An Integrated Analysis of Cardiac Output and Muscle Oxidative Capacity on Exercise Performance in Adolescents - Zhang, Zhanshuo (Exploring Science Academic Conference Series, 2026)
The cardiovascular and muscular developing systems during adolescence are considered to be a critical period in the physiological basis of the long -term exercise capacity and health. This research seeks to examine how cardiac output and muscle oxidative capacity work together to influence exercise performance in teenagers in a systems approach. It claims that performance in exercise is not governed by one limiting factor, but is the interaction between oxygen delivery and oxygen utilization systems. The stu dy shows that the performance limitation can alternatively be between central and peripheral system based on their relative developmental level through theoretical analysis and case examples through the conceptual illustrations. In case of inadequate cardiac output, oxygen delivery makes the limiting factor that limits aerobic performance in spite of muscular capacity. On the other hand, in cases where the delivery of oxygen is normal and the oxidative capacity of the muscle is small, inefficient use of oxygen causes premature fatigue and low endurance. The analysis also points out that the combined development of the systems and their coordinated operation is a way to reach optimal performance. Despite having a well -organized conceptual framework, the study is constrained by lack of empirical validation. Future studies need to be experimental and longitudinal to test and refine further this combined framework in adolescence population.